PARP inhibitors promote stromal fibroblast activation by enhancing CCL5 autocrine signaling in ovarian cancer - Xiaoting Li (Nature Portfolio, 2021)
Abstract Cancer-associated fibroblasts (CAFs) play significant roles in drug resistance through different ways. Antitumor therapies, including molecular targeted interventions, not only effect tumor cells but also modulate the phenotype and characteristics of CAFs, which can in turn blunt the therapeutic response. Little is known about how stromal fibroblasts respond to poly (ADP-ribose) polymerase inhibitors (PARPis) in ovarian cancer (OC) and subsequent effects on tumor cells. This is a study to evaluate how CAFs react to PARPis and their potential influence on PARPi resistance in OC. We discovered that OC stromal fibroblasts exhibited intrinsic resistance to PARPis and were further activated after the administration of PARPis. PARPi-challenged fibroblasts displayed a specific secretory profile characterized by increased secretion of CCL5, MIP-3α, MCP3, CCL11, and ENA-78. Mechanistically, increased secretion of CCL5 through activation of the NF-κB signaling pathway was required for PARPi-induced stromal fibroblast activation in an autocrine manner. Moreover, neutralizing CCL5 partly reversed PARPi-induced fibroblast activation and boosted the tumor inhibitory effect of PARPis in both BRCA1/2-mutant and BRCA1/2-wild type xenograft models. Our study revealed that PARPis could maintain and improve stromal fibroblast activation involving CCL5 autocrine upregulation. Targeting CCL5 might offer a new treatment modality in overcoming the reality of PARPi resistance in OC.